SMK3 Stress Diagnosis Survey for First-Line Management Employees at PT. X - Maulana Seftian; Lucia Vega Tri Krismastuti; Hurriyah Gayo; Rilla Sovitriana (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study aims to diagnose the level of work-related stress among first-line management employees at PT. X as part of the compliance with the Occupational Safety and Health Management System (SMK3) regulations, in accordance with Government Regulation No. 50 of 2012 and the Minister of Manpower Regulation No. 5 of 2018. A descriptive quantitative approach was employed using purposive sampling, involving 20 respondents from both the head office and branch office. The instrument used was a questionnaire based on the Ivancevich and Matteson (1980) stress scale, covering six dimensions of work stress: role ambiguity, role conflict, quantitative workload, qualitative workload, career development, and responsibility for others. The analysis revealed that the majority of respondents experienced moderate levels of work stress, with the highest prevalence found in the dimensions of career development (85%), qualitative workload (75%), and role conflict (60%). Additionally, 10% of respondents were identified as experiencing severe stress, particularly in the qualitative workload dimension. Based on these findings, an intervention plan was developed, including competency enhancement training, updated work procedures, psychological counseling, and optimization of organizational communication. This study highlights the importance of regular psychological monitoring in the workplace as a preventive effort to mitigate productivity decline and promote employee well-being.